Gabon : Request for a Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2020)
The COVID-19 pandemic and concurrent collapse in oil prices are expected to put the economy under extreme stress, particularly in a context of limited buffers. Economic growth will slow, and the fiscal and external positions will weaken, creating significant additional financing needs in 2020.